Bowel Perforation During Haemophagocytic Lymphohistiocytosis Treatment with Corticosteroids and Anakinra - Jan Adamski (SMC MEDIA SRL, 2021)
We report the use of anakinra to treat a case of a 64-year-old man diagnosed with hemophagocytic lymphohistiocytosis (HLH) with neurological involvement. After the administration of intravenous pulse corticosteroid therapy, immunoglobulin, and anakinra, the patient showed neurological recovery. However, the recovery was complicated by the perforation of a pre-existing bowel diverticulum. The effect of anakinra on bowel inflammation has not yet been clearly established. It can potentially augment bowel inflammation and contribute to the risk of bowel perforation associated with the concomitant use of corticosteroids.